2021
DOI: 10.3390/su132112217
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment and Air Quality Study during Different Phases of COVID-19 Lockdown in an Urban Area of Klang Valley, Malaysia

Abstract: Globally, the COVID-19 pandemic has had both positive and negative impacts on humans and the environment. In general, a positive impact can be seen on the environment, especially in regard to air quality. This positive impact on air quality around the world is a result of movement control orders (MCO) or lockdowns, which were carried out to reduce the cases of COVID-19 around the world. Nevertheless, data on the effects on air quality both during and post lockdown at local scales are still sparse. Here, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…First, regarding the effect on production, the evidence of the initial periods of confinement in different cities and countries showed a relevant decrease in the pollution in urban and rural zones [49,50]. For example, recent research suggests that lockdowns and other restrictions related to COVID-19 have had a positive impact on terms of air quality in countries such as China [51,52], Italy [53,54], Portugal [50], the United States [49], India [55], and Malaysia [56]. In this vein and linked to the idea of sustainable consumption and emissions of waste and pollutants, scholars have suggested that the control of governments, manifested in restrictions on industry emissions and transport, can be the bridge to reaching environmental goals regarding air quality [56].…”
Section: Covid-19 Pandemic (Cov) and Sustainable Consumption (Sc)mentioning
confidence: 99%
See 2 more Smart Citations
“…First, regarding the effect on production, the evidence of the initial periods of confinement in different cities and countries showed a relevant decrease in the pollution in urban and rural zones [49,50]. For example, recent research suggests that lockdowns and other restrictions related to COVID-19 have had a positive impact on terms of air quality in countries such as China [51,52], Italy [53,54], Portugal [50], the United States [49], India [55], and Malaysia [56]. In this vein and linked to the idea of sustainable consumption and emissions of waste and pollutants, scholars have suggested that the control of governments, manifested in restrictions on industry emissions and transport, can be the bridge to reaching environmental goals regarding air quality [56].…”
Section: Covid-19 Pandemic (Cov) and Sustainable Consumption (Sc)mentioning
confidence: 99%
“…For example, recent research suggests that lockdowns and other restrictions related to COVID-19 have had a positive impact on terms of air quality in countries such as China [51,52], Italy [53,54], Portugal [50], the United States [49], India [55], and Malaysia [56]. In this vein and linked to the idea of sustainable consumption and emissions of waste and pollutants, scholars have suggested that the control of governments, manifested in restrictions on industry emissions and transport, can be the bridge to reaching environmental goals regarding air quality [56]. Nonetheless, those findings should be assessed with caution because they are concluded under exceptional circumstances.…”
Section: Covid-19 Pandemic (Cov) and Sustainable Consumption (Sc)mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, those stations with shorter dependencies on their previous values will have more volatile PM 10 values. These different dependencies of hourly PM 10 time series on its previous values for each station could be caused by several factors such as wind speed, humidity, temperature, land terrain and activities in that area [19][20][21].…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Several interesting findings were achieved within the reviewed papers, demonstrating the potentiality of LC networks to greatly expand the air quality monitoring capability. LC networks allowed, for example, investigating ship emissions in harbour areas (Jayaratne et al, 2020; Merico et al, 2019), identifying restaurants as an important local contributor to PM 2.5 concentrations (Eilenberg et al, 2020; Kosmopoulos et al, 2022), finding that local sources are responsible for only a fraction (30%) of the total PM 2.5 in the urban core while the rest is transported from other areas (Kosmopoulos et al, 2022), identifying the best hours to practice physical activities in the open air (Nieckarz & Zoladz, 2020), improving air pollution monitoring during special events (Chao et al, 2021; Kuhn et al, 2021), and evaluating the impact on air quality of the Covid‐19 pandemic (Chadwick et al, 2021; Davidović et al, 2021; Mohd Nadzir et al, 2021; Mousavi & Wu, 2021), forest fires (Stavroulas et al, 2020), fireworks (Petäjä et al, 2021), a stone quarry (Molho et al, 2019) and a volcano (Whitty et al, 2020).…”
Section: Discussionmentioning
confidence: 99%